Large-scale Cosmic-ray Anisotropies with 19 yr of Data from the Pierre Auger Observatory - A. Abdul Halim; P. Abreu; M. Aglietta; I. Allekotte; K. Almeida Cheminant; A. Almela; R. Aloisio; J. Alvarez-Muñiz; A. Ambrosone; J. Ammerman Yebra; G. A. Anastasi; L. Anchordoqui; et al. (The Astrophysical Journal)
Results are presented for the measurement of large-scale anisotropies in the arrival directions of ultra–high-energy cosmic rays detected at the Pierre Auger Observatory during 19 yr of operation, prior to AugerPrime, the upgrade of the observatory. The 3D dipole amplitude and direction are reconstructed above 4 EeV in four energy bins. Besides the established dipolar anisotropy in R.A. above 8 EeV, the Fourier amplitude of the 8–16 EeV energy bin is now also above the 5 σ discovery level. No time variation of the dipole moment above 8 EeV is found, setting an upper limit to the rate of change of such variations of 0.3% yr ^−1 at the 95% confidence level. Additionally, the results for the angular power spectrum are shown, demonstrating no other statistically significant multipoles. The results for the equatorial dipole component down to 0.03 EeV are presented, using for the first time a data set obtained with a trigger that has been optimized for lower energies. Finally, model predictions are discussed and compared with observations, based on two source emission scenarios obtained in the combined fit of spectrum and composition above 0.6 EeV.